Cytoflavin in Polychemotherapy of Breast Cancer - V. A. Kashuro; S. I. Glushkov; S. N. Zheregelya (Антибиотики и Химиотерапия)
The efficacy of cytoflavin as a supporting drug in the CAF chemotherapy of breast cancer was studied. It was estimated by the tolerability, the peripheric blood index dynamics, the patients general condition (Karnovsky Index) and the frequency of the side effects. For the immediate estimation of the polychemotherapy and cytoflavin effects on the cytoprotection natural system state, the dynamics of the glutathione metabolism and the lipid peroxidation in the erythrocytes was investigated.